Environmental impact assessment of leachate from mining tailings using electrical resistivity imaging - Mosaad Ali Hussein Ali; Wei Qian; Ragab Rabeiy; Hussein A. Saleem; Ahmed S. Mohamed; Abdullahi Uwaisu Muhammad; Ali Shebl (Scientific Reports)
Abstract The environmental difficulties from mining tailings arise mainly from legacy dump sites because these residues spread pollution through surrounding areas. Effective environmental management requires a comprehensive pre-assessment. An ERI, electrical resistivity imaging, system serves as the analytical tool to create models for leachate assessment prior to its measurement in abandoned mining tailing storage sites. A total of 16 2D ERI profiles produced both 2D and 3D models that monitored the El Mochito mine waste site in Honduras. Different geoelectric zones were identified in the electrical resistivity models of this site with high resistivity values ranging between 60 and 100 Ω m in the surface layer while the middle layer exhibited moderate resistivity between 30 and 60 Ω m and the lowest resistivity of 1–30 Ω m was observed in the active leaching zone that contained conductive materials and mineral-rich leachate. The 3D hydrogeological models provided clear visibility of leachate areas and flow paths. The leachate migration showed uniform movement towards the northern direction until it reached the southern region where concentrations decreased. Another level of spatial understanding and depth information on resistivity distribution was obtained from 3D ERI models. The complete assessment objectives of the research form the basis for future investigations while demonstrating the importance of integrating geochemical measurements. The study emphasizes the need for ERI to examine complicated mining tailings yet requests deeper scientific investigation to create effective environmental management techniques and remediation practices.